2010
DOI: 10.1007/s10800-009-0069-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an electrochemical reactor for the ozone production in electrolyte-free water

Abstract: The filter-press electrochemical ozonizer is characterized as a function of the applied electric current, temperature, and linear velocity of the electrolyte-free water. Lead dioxide electroformed on surface of a nonplatinized fine mesh stainless steel support was used as anode. Electrolysis of the electrolyte-free water was carried out using the membrane electrode assembly (MEA) adequately compressed by means of a specially designed clamping system. Electrochemical characterization studies were carried out ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Glycolipids, glycoprotein, and certain amino acids such as tryptophan in the bacterial membrane are first attacked by ozone. Alteration of sulfhydryl groups results in bacterial cell disruption (da Silva, Franco, Sousa, & Goncalves, ), with enhanced cell permeability and lysis. This phenomenon often leads to bacterial death.…”
Section: Ozonificationmentioning
confidence: 99%
“…Glycolipids, glycoprotein, and certain amino acids such as tryptophan in the bacterial membrane are first attacked by ozone. Alteration of sulfhydryl groups results in bacterial cell disruption (da Silva, Franco, Sousa, & Goncalves, ), with enhanced cell permeability and lysis. This phenomenon often leads to bacterial death.…”
Section: Ozonificationmentioning
confidence: 99%
“…Its main advantage is that it does not form noxious residues in treated water. Perfluorinated membranes are used in PEM ozone generators [151,152]. Porous platinum typically serves as the cathode.…”
Section: Membrane Electrolysis Technologies Under Developmentmentioning
confidence: 99%
“…Limited studies on the electrochemical degradation of synthetic textile effluent by Sn/Sb/Ni-Ti anodes can be found in literature. In these studies, it is reported that 80-90% of COD and color removal is possible (Parsa and Abbasi, 2012;Zakaria and Christensen, 2014;da Silva and Jardim, 2006;Da Silva et al, 2010;Stucki et al, 1987;Cui et al, 2009;Naumczyk et al, 1996;Korbahti and Tanyolac, 2008;Nordin et al, 2013). Direct anodic oxidation is also too limited in these studies.…”
Section: Investigation Of Electrochemical Color Removal From Oid Wastmentioning
confidence: 99%